Applied drilling circulation systems : hydraulics, calculations, and models - Guo, Boyun (Gulf Professional Pub., 2011)
Used to clean the borehole, stabilize rock, control pressures, or enhance drilling rates, drilling fluids and their circulation systems are used in all phases of a drilling operation. These systems are highly dynamic and complicated to model until now. Written by an author with over 25 years of experience, Applied Drilling Circulation Systems: Hydraulics, Calculations and Models provide users with the necessary analytical/numerical models to handle problems associated with the design and optimization of cost-effective drilling circulation systems. The only book which combines system modeling, design, and equipment, Applied Drilling Circulation Systems: Hydraulics, Calculations and Models provides a clear and rigorous exposition of traditional and non-traditional circulation systems and equipment followed by self contained chapters concerning system modelling applications. Theories are illustrated by case studies based on the author's real life experience. The book is accompanied by a website which permits readers to construct, validate, and run models employing Newtonian fluids, Bingham Plastic fluids, Power Law fluids, and aerated fluids principles. This combination book and website arrangement will prove particularly useful to drilling and production engineers who need to plan operations including pipe-tripping, running-in casing, and cementing. In-depth coverage of both on- and offshore drilling hydraulics. Methods for optimizing both on- and offshore drilling hydraulics. Contains problems and solutions based on years of experience.